Tutorial: Speech Assessment for Multilingual Children Who Do Not Speak the Same Language(s) as the Speech-Language Pathologist - McLeod, Sharynne; Verdon, Sarah (American journal of speech-language pathology, 2017)
The aim of this tutorial is to support speech-language pathologists (SLPs) undertaking assessments of multilingual children with suspected speech sound disorders, particularly children who speak languages that are not shared with their SLP. The tutorial was written by the International Expert Panel on Multilingual Children's Speech, which comprises 46 researchers (SLPs, linguists, phoneticians, and speech scientists) who have worked in 43 countries and used 27 languages in professional practice. Seventeen panel members met for a 1-day workshop to identify key points for inclusion in the tutorial, 26 panel members contributed to writing this tutorial, and 34 members contributed to revising this tutorial online (some members contributed to more than 1 task). This tutorial draws on international research evidence and professional expertise to provide a comprehensive overview of working with multilingual children with suspected speech sound disorders. This overview addresses referral, case history, assessment, analysis, diagnosis, and goal setting and the SLP's cultural competence and preparation for working with interpreters and multicultural support workers and dealing with organizational and government barriers to and facilitators of culturally competent practice. The issues raised in this tutorial are applied in a hypothetical case study of an English-speaking SLP's assessment of a multilingual Cantonese- and English-speaking 4-year-old boy. Resources are listed throughout the tutorial.